Village fund management accountability in Kleseleon village, Weliman district, Malaka regency - Ade Sjan Maikameng; William Djani; Hendrik Toda (goodwood publishing, 2020)
Purpose: This study analyzes the accountability of village fund management in Kleseleon village, Weliman district, Malaka regency. Research methodology: This is qualitative research with a case study approach. Data were collected through observation, interviews and document searches. Results: There are several problems in managing village funds in Kleseon village, such as delays in determining the program to inefficient reporting. The inhibiting factors for the accountability of village financial management in Kleseleon village are (1) delays in village annual development planning, (2) human resources, (3) facilities, (4) delays in budget allocation and (5) delays in the availability of funds, general guidelines and technical guidelines. Limitations: This research was conducted relatively quickly so that researchers could not examine more deeply related to the existing problems. Contribution: The research findings can be used as evaluation material for the Kleseon village government in managing village funds.